2021
DOI: 10.1021/jacs.1c04493
|View full text |Cite
|
Sign up to set email alerts
|

Ir-Catalyzed Regio- and Enantioselective Hydroalkynylation of Trisubstituted Alkene to Access All-Carbon Quaternary Stereocenters

Abstract: The stereoselective construction of all-carbon quaternary stereocenters, especially acyclic ones, represents an important challenge in organic synthesis. In particular, homopropargyl amides with a quaternary stereocenter β to a nitrogen atom are valuable synthetic intermediates, which could be transformed to diverse chiral structures through alkyne transformations. However, highly enantioselective synthetic methods for homopropargyl amides with a β quaternary stereocenter are extremely rare. We report here unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 114 publications
0
19
0
1
Order By: Relevance
“…In contrast, in the presence of electron-rich ligand L14, homopropargyl amides 95 with a  all-carbon quaternary center were obtained in both high yield and high enantioselectivity, albeit with a small amount of -alkynylation products (Scheme 20). 42 Computational studies indicated that the ligand is crucial for controlling the regioselectivity of the hydroalkynylation of ,-disubstituted enamides. The phosphoramidite ligand is less electron-donating than a bisphosphine ligand, so the electron density at the metal center is reduced, which is conducive to the reductive elimination of the iridium center, leading to the formation of the -hydroalkynylation product.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…In contrast, in the presence of electron-rich ligand L14, homopropargyl amides 95 with a  all-carbon quaternary center were obtained in both high yield and high enantioselectivity, albeit with a small amount of -alkynylation products (Scheme 20). 42 Computational studies indicated that the ligand is crucial for controlling the regioselectivity of the hydroalkynylation of ,-disubstituted enamides. The phosphoramidite ligand is less electron-donating than a bisphosphine ligand, so the electron density at the metal center is reduced, which is conducive to the reductive elimination of the iridium center, leading to the formation of the -hydroalkynylation product.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…In this regard, Li and co-workers developed a substrate-directed regio-and enantioselective hydroalkynylation of trisubstituted alkenes (Scheme 28). 40 The catalytic C-C formation preferentially occurs at the more hindered position, generating acyclic quaternary carbon stereocenters  to an amide. Through a sequence of alkene hydroalkynylation and alkyne functionalization, diverse products containing quaternary carbon stereocenters were prepared.…”
Section: Scheme 27 Cu-catalyzed Dicarbofunctionalization Of -Unsatu...mentioning
confidence: 99%
“…8 To date, density functional theory (DFT) calculations have been used to perform mechanistic studies on transition metal complex-catalyzed dehydrogenation reactions to obtain new C(sp)-C, C(sp)-B, and C(sp)-Sn bonds as coupling products. [9][10][11] Obviously, dehydrogenative couplings catalyzed by transition metals to synthesize new alkynes are more atomically efficient when compared with traditional methods, but transition metal catalysts are usually expensive and environmentally unfriendly. Therefore, scientists are diligently working to find new catalytic systems with low cost, eco-friendliness, and high selectivity.…”
Section: Introductionmentioning
confidence: 99%